Building Further on the Situational Theory of Publics: Theoretical Evolution to Situational Theory of Problem Solving and Future Research - Kim, Jeong-Nam (Institutional Knowledge at Singapore Management University, 2014)
Defining and identifying publics is crucial to PR research and practice. Despite this importance, it is rare to find scholarly works that have refined the concepts and frameworks of James Grunig’s Situational Theory of Publics, which has contributed to the development of PR theories on publics and their behaviors for decades. Thus, this present study aims to review the history, development, and extension of Grunig’s Situational Theory. Specifically, this study discusses conceptual origin and theoretical base of Situational Theory of Publics since 1966 and reviews evolutionary process to Situational Theory of Problem Solving. In addition, this study discusses how Situational Theory of Problem Solving can contribute to the understanding of public’s communicative actions and to the methods of public segmentation in our digitalized, networked society and the arrival of social media era. This present study lays the ground for the further development of future PR research and practices by proposing future research directions and applications of Situational Theory of Problem Solving in various areas.